Self-medication for oral health problems in COVID-19 outbreak : prevalence and associated factors = Automedicación para enfermedades orales durante la pandemia del COVID-19 : prevalencia y factores asociados - Alavi Namvar, Mahsa
This study aimed to investigate self-medication in the COVID-19 outbreak among patients attending the dental clinic of Zanjan University of Medical Sciences. The total number of patients who took part in this research was 306, and they were questioned using a 28-item questionnaire after signing a permission form. SPSS26 was used to gather and analyze the data. There were 196 women and 110 males among the patients.The results showed that the prevalence of self-medication was 53.9%, and a lower educational level was associated with self-medication. The most common problem for self-medicating was toothache, and the most frequent drug was Ibuprofen. The majority of the participants reported that their relatives/friends suggested the drugs to them. The main source of obtaining the drugs was pharmacies. The major reasons for self-medication were the high cost of dental treatments and fear of COVID-19.